Investigating Difficulties Faced by Iraqi EFL Learners in Identifying the Illocutionary Force of the Reduplicative Words (Journal of the College of Education for Women, 2019)
A reduplicative word is an important phenomenon in all language studies because it reflects many functions in language communication such as plurality, emphasis, contrast, imitation. The various instances of reduplicative words in a particular language reflect the richness and uniqueness of that language. Moreover, such variation gives insights into both culture and thought. A reduplicative word is a linguistic phenomenon found in the syntactic, morphological, phonological and semantic levels. The current study aims at investigating the illocutionary force of English reduplicative words in some selected English colloquial utterances. To achieve this aim, an analytical -pragmatic approach has been used by adopting Searle’s (1979) classifications of speech acts in order to identify and analyze the illocutionary force of reduplicative words. The results show that EFL learners face difficulties in identifying the illocutionary forces because of the lack of the cultural background concerning these reduplicative words. The majority of errors committed by the participants are found in production test due to the fact that Iraqi EFL learners are ignorant and unfamiliar with producing such words as well as these words require much more awareness, attention and practice.Finally, they have committed less errors in the recognition test due to the fact that they have somehow pragmatic competence and background knowledge regarding these words.